Pandora Papers and the latest European efforts to combat money laundering, tax evasion and tax avoidance - Mănescu, Dragoș Mihail (Technium Social Sciences Journal, 2022)
Following the revelations of the Pandora Papers on offshore financial mechanisms which allow European citizens to avoid paying tax obligations and to commit tax evasion or money laundering offenses, the European Parliament adopted Resolution 2021/2922 (RSP) requiring Member States to take urgent and decisive action, both legislative and investigative, to combat this type of criminal behavior. As a response to the request formulated by the Parliament, the European Commission drafted a Proposal for a council Directive laying down rules to prevent the misuse of shell entities for tax purposes by introducing new monitoring and reporting regulations.